THE ROLE OF STIMULUS-ORGANISMRESPONSE (SOR) IN E-COMMERCE STRATEGIC DECISION MAKING FOR SUSTAINABILITY - Cakraputri, Dayaningtias
Given the rapid evolution of the e-commerce landscape, businesses are presented with the important task of embracing sustainable practices. This thesis delves into the vital role played by the Stimulus-Organism-Response (SOR) framework in facilitating strategic decision-making processes within the realm of e-commerce for sustainability. The SOR model examines the relationship between e-commerce livestreaming, customer engagement, value co-creation, and customer loyalty. This paper aims to explore the evolution from e-commerce livestreaming to customer loyalty by studying how these factors are perceived and understood by decisionmakers in e-commerce companies. This data collected from an online questionnaire for the research was through a survey involving 1282 respondent and 11 participants for the qualitative supporting data. The study utilizes Structural Equation Modelling (SEM) Lisrel for empirical analysis and IBM SPSS Statistic 8.8 for data analysis. The findings indicate that customer engagement is most impacted by factors such as aesthetic appeal, functional layout, financial security, and verbal communication. Nonverbal communication and service skills, on the other hand, do not seem to have a significant impact on customer engagement.In terms of value co-creation, customer engagement directly influences functional, hedonic, and social values, which all directly impact customer loyalty. Customer engagement and value cocreation serve as mediating factors between e-commerce livestreaming and customer loyalty. The research results highlight the effects of e-commerce livestreaming, provide a new perspective on applying the SOR theory to ecommerce, and illustrate how livestreaming enhances visual appeal and personalized experiences for customers while improving the communication skills of operations and service staff. By shedding light on the significance of the SOR framework in guiding strategic decision-making, this thesis establishes a theoretical basis for practitioners and policymakers who are interested in promoting sustainability within the e-commerce sector. Ultimately, the goal of this research is to facilitate the creation of more informed, adaptable, and sustainable strategies that are in line with the changing dynamics of the e-commerce industry.